Hubungan antara Faktor Karakteristik Petani dengan Tingkat Adopsi Budidaya Padi Varietas Ciherang di Kabupaten Bangkalan - Cut Adira Titania Putri; Sugihardjo Sugihardjo; Eny Lestari (Universitas Sebelas Maret, 2024)
The Ciherang variety developed by the Department of Agriculture’s Research Center is useful for increasing rice productivity and obtaining varieties that are resistant to pests and diseases. Bangkalan Regency seeks to support agricultural development by introducing the Ciherang variety as a step to increase production and the welfare of farmers in the region. The ability to accept an idea is different for each individual, including farmers. Therefore, this study needs to be conducted to determine the factors of farmer characteristics in the level of adoption of Ciherang rice cultivation in Bangkalan Regency. This study aimed to determine the relationship between farmer characteristic factors and the level of adoption of Ciherang rice cultivation in Bangkalan Regency. This research uses quantitative methods, including field survey techniques and purposive sampling techniques, to determine the research location in Bangkalan Regency. The research sample was taken as many as 60 farmers using proportional random sampling technique. Data analysis in this study used the Spearman rank correlation test. The results showed that internal and external factors of farmer characteristics in the form of age, education level, farming experience, land tenure status, and information sources have a significant correlation to the level of adoption of Ciherang rice cultivation in Bangkalan Regency. In contrast, farm size and extension worker intensity do not have a significant correlation with the level of adoption of Ciherang rice cultivation in Bangkalan Regency.